ChemInform Abstract: Synthesis of 2H‐Azirines by Iridium‐Catalyzed Decarboxylative Ring Contraction of Isoxazol‐5(4H)‐ones. Issue 42 (September 2016) - Okamoto, Kazuhiro; Shimbayashi, Takuya; Yoshida, Masato; Nanya, Atsushi; Ohe, Kouichi
Abstract: under phosphine‐free and environmentally benign conditions